Mathematics Standard Level course companion - Buchanan, Laurie, 1970-; Fensom, Jim.; Kemp, Ed.; International Baccalaureate (Foundation) (Oxford : Oxford University Press, 2012)
Presents a comprehensive overview of the IB Mathematics Standard Level 2012 syllabus, providing more than seven hundred pages of practice and challenge, and covering all topics and the new internal assessment.
"In cooperation with ib"--T.p.
Includes index.
Adult
Adult
System requirements for PC and Mac on disc label.
Keywords: International baccalaureate -- Study guides; Mathematics -- Examinations -- Study guides; Mathematics -- Study and teaching (Secondary); International baccalaureate -- Study guides; Mathematics -- Examinations -- Study guides; Mathematics -- Study and teaching; Secondary education